Applicability of Moyers and Tanaka-Johnston analyses for the Arab population of Pekalongan, Indonesia - Fani Tuti Handayani; Rizky Amalia Hidayah (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: The Moyers and Tanaka-Johnston analyses, both of which were developed through research into the Nordic-Caucasoid population, constitute the most widely used non-radiographic mixed dentition analyses. Application of these prediction methods to other populations has been extensively investigated, although their suitability to the Arab population resident in Indonesia has rarely been studied. Purpose: This study aimed to investigate the reliability of Moyers and Tanaka-Johnston analyses of the Arab population of Pekalongan, a city in Central Java, Indonesia. Methods: This research constituted an observational study incorporating a cross-sectional design of 33 subjects who willingly signed an informed consent form. Their actual tooth size was determined in accordance with the inclusion criteria and then compared with the predictive tooth size values of the Moyers and Tanaka-Johnston analyses. Results: Comparison of mean values indicated that the predictive values of Moyers 75% (YM) and Tanaka-Johnston (YT) were higher than the actual value (Y). The reliability test result confirmed a value of k = 0.026 for the Y-YM ratio; and k = 0.025 for YT-Y ratio. The calculation results for the mandible indicated a k-value of 0.000 for both types of comparisons between YM-Y and YT-Y. The Moyers 75% prediction for maxilla had a higher reliability value than that of Tanaka-Johnston. The Shapiro-Wilk normality test applied to Y, YM, and YT in the maxilla and mandible indicated that data was normally distributed (sig > 0.05). A Levene's test of homogeneity was conducted and produced homogeneous data (sig > 0.05) with values of 0.333 for Y, 0.516 for YM, and 1.000 for YT. An ANOVA test showed Y-YM and Y-YT to have insignificant differences (p<0.05). This result caused comparative tests to determine both analysis eminence in predicting canine and premolar values according to the study sample not conducted. Conclusion: The Moyers 75% and Tanaka-Johnston analyses were reliable because the values produced differed slightly from the actual values. This study concluded that Moyers and Tanaka-Johnston analyses remain valid means of calculating mixed dentitions.